2009
DOI: 10.1007/s00425-008-0876-0
|View full text |Cite
|
Sign up to set email alerts
|

An anionic class III peroxidase from zucchini may regulate hypocotyl elongation through its auxin oxidase activity

Abstract: The high number of peroxidase genes explains the description of numerous physiological functions and the fact that the in planta function of a single isoform has never been characterized yet. We analyzed in transgenic Arabidopsis thaliana the localization of a zucchini isoperoxidase (APRX), previously puriWed thanks to its pectin binding ability. We conWrmed that the protein is localized near the cell wall, mainly produced in the elongation area of the hypocotyls and respond to exogenous auxin. In addition, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(31 citation statements)
references
References 65 publications
2
25
0
1
Order By: Relevance
“…LCYb (lycopene beta cyclase) and PSY (phytoene synthase) were also chosen as important enzymes involved in the carotenoid biosynthesis pathway [27]. The last one was the APRX gene, a gene encoding a peroxidase and that seems to have an important function in the growth and development of the plant [28].…”
Section: Resultsmentioning
confidence: 99%
“…LCYb (lycopene beta cyclase) and PSY (phytoene synthase) were also chosen as important enzymes involved in the carotenoid biosynthesis pathway [27]. The last one was the APRX gene, a gene encoding a peroxidase and that seems to have an important function in the growth and development of the plant [28].…”
Section: Resultsmentioning
confidence: 99%
“…Peroxidase activity is also related to cell stem maintenance and cell division and differentiation in the root meristem (Jiang and Feldman, 2005;Tsukagoshi et al, 2010). It is remarkable that plant peroxidase activities have the ability to catalyze IAA (Gazaryan et al, 1996;Cosio et al, 2009), reducing the active auxin pool. Overexpression of an anionic PER in tobacco (Nicotiana tabacum) plants repressed LR formation, likely by oxidizing the IAA and reducing the active auxin needed for the formation of the lateral primordia (Lagrimini et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…[56][57][58] As a second possibility, peroxidases can induce cell growth also through IAA signaling pathways. 46 i.e., Cosio et al 24 found that transgenic Arabidopsis constitutively expressing a zucchini peroxidase, which showed an auxin oxidase activity in vitro, exhibited longer hypocotyl lengths than wild-type plants.…”
Section: Methodsmentioning
confidence: 99%